Charting New Horizons in Family Tourism Entrepreneurship and Sustainability: Women in Business Succession - Dan, Nurzafirah; Shimizu, Tetsuo; Mohd, Nur Shuhadah (Springer Nature Switzerland AG, 2024)
Women’s involvement in family tourismbusiness succession, despite their pivotal entrepreneurial commitment conducive to organizational sustainability, remains inadequately explored. This study endeavors to promote the utilization of family entrepreneurial resources and women’s entrepreneurial orientation as pivotal facilitators for their integration into business succession, serving as antecedents for sustainability. Qualitatively conducted on Tioman Island, 11 women-led family businesses participated in in-depth interviews, selected through purposive and snow ball sampling methods. Thematic analysis revealed key themes of entrepreneurial resources encompassing family business and socioemotional wealth, cumulative entrepreneurship experience and moulding entrepreneurial stewardship; women’s entrepreneurial orientation comprising risk-taking, competitive aggressiveness,and proactive adaptability. The study emphasizes the significance of family tourism entrepreneurial resources in easing the path for women in succession. It highlights how women’s entrepreneurial orientation profoundly impacts business succession and the enduring success of family businesses. By nurturing these aspects, it advocates for a more inclusive and sustainable landscape within the tourism industry, promising a more prosperous future.